2022
DOI: 10.1038/s41598-022-20875-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of the bowfin (Amia calva) reveals unrecognized species diversity in a living fossil lineage

Abstract: The Bowfin (Amia calva), as currently recognized, represents the sole living member of the family Amiidae, which dates back to approximately 150 Ma. Prior to 1896, 13 species of extant Bowfins had been described, but these were all placed into a single species with no rationale or analysis given. This situation has persisted until the present day, with little attention given to re-evaluation of those previously described nominal forms. Here, we present a phylogenomic analysis based on over 21,000 single nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…Our study reveals the presence of two recently diverged sibling species of bowfins. A recent study using ddRAD data, but with very limited sampling of A. calva and A. ocellicauda, concluded that there may be up to four living species of Amia [24]. With a more inclusive sampling of populations (figure 1a), our genomic analyses consistently delimit two species of Amia.…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…Our study reveals the presence of two recently diverged sibling species of bowfins. A recent study using ddRAD data, but with very limited sampling of A. calva and A. ocellicauda, concluded that there may be up to four living species of Amia [24]. With a more inclusive sampling of populations (figure 1a), our genomic analyses consistently delimit two species of Amia.…”
Section: Resultssupporting
confidence: 57%
“…With a more inclusive sampling of populations (figure 1a), our genomic analyses consistently delimit two species of Amia. The populations within either species that exhibit the greatest genetic divergence are those of A. calva from Florida and the Gulf Coast, which were not sampled in the other study [24]. In addition, the shape of the IO and the number of dentary teeth delimit two living species of Amia (figure 1d; electronic supplementary material, table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Extant holosteans include seven species of Lepisosteidae (gar; (Eschmeyer 1998)) and two species of Amiidae (bowfin; (Brownstein et al 2022; Wright et al 2022)). Analyses of the spotted gar ( Lepisosteus oculatus ) genome demonstrated the potential of holostean genomes for comparative studies, providing critical insights into the evolution of vertebrate immunity, development, and the function of regulatory sequences (Braasch et al 2016).…”
Section: Introductionmentioning
confidence: 99%